Impact of Reproductive Health Counseling on Premarital Women's Knowledge Regarding Healthy Pregnancy Preparation: A Study in Tlogosuryo, Malang - Putri Eka Sejati; Theresia Jebe Kleden; Reni Yuli Astutik; Candra Wahyuni (Journal for Research in Public Health, 2026)
High maternal mortality highlights the need for premarital reproductive health counseling. This study evaluated its impact on healthy pregnancy preparation knowledge in Malang. A pre-experimental design sampled 35 premarital women (Jan–Feb 2026). The intervention was a 90-minute session covering maternal nutrition, reproductive health, and danger signs. Data were analyzed using the Wilcoxon signed-rank test. Pre-counseling, 68.6% of respondents had poor knowledge. Post-counseling, 80.0% achieved good knowledge. The Wilcoxon test yielded a significant p-value of 0.000 (p < 0.05), demonstrating that reproductive health counseling exerts a significant positive effect on enhancing knowledge.Structured premarital counseling effectively mitigates knowledge gaps. Active participation is highly recommended to improve maternal outcomes.